Evaluating performance to improve the level of the University of Baghdad in the QS ranking: a comparative study of the University of Baghdad with some local, Arab, and international universities (Entrepreneurship Journal for Finance and Business, 2024)
The research aims to identify the criteria that contributed to the entry of the University of Baghdad into the (QS ranking) for the year 2024, as well as to identify the strengths and weaknesses in the university's performance locally, regionally, and globally. It also aims to establish a set of mechanisms and procedures followed by the university to develop and improve its competitive position within global rankings. The research problem is that there is a weak ranking level in the QS classification of the University of Baghdad. The comparative method was adopted as the appropriate approach for the research orientations and achieving its goals. The study community included universities listed in the global (QS ranking), with the research sample being one of the Iraqi universities, the University of Baghdad. A benchmarking comparison was conducted with Al-Mustansiriya University locally, King Faisal University regionally, and the University of Florida globally. The most important results of the research indicate that the University of Baghdad excelled locally in the areas of academic reputation by a margin of (5.8%), employment by a margin of (6.1%), and research citations by a margin of (0.2%). Regionally, the university excelled in the area of graduate employment by a margin of (2.8%) and the ratio of professors to students by a margin of (19.5%). However, globally, the university did not excel in any of the indicators of the global QS ranking. A set of mechanisms was proposed to improve the performance of the University of Baghdad in the QS ranking, including the necessity of publishing research in reputable international journals to enhance its academic reputation regionally and globally.